Glee [compact disc] : the music presents the Warblers. (Columbia, 2011)
More great music from the hit TV show Glee. These tunes are performed by the fictional high school singing group from Dalton Academy, the Warblers. The songs are performed by Darren Criss, Chris Colfer and the Tufts University Beelzebubs.